Strategic Role of Supply Chain Performance Measurement in Enhancing Organizational Competitiveness: An Integrative Review - Setyorini, Retno; Rahayu, Agus; Wibowo, Lili Adi; Sultan, Mokh. Adib (Journal of Ecohumanism, 2025)
This research aimed to measure supply chain performance using a bibliometric analysis method. By examining a collection of scientific articles published between 2014 and 2023, the analysis identified evolving trends, central themes, and gaps in the field. The results showed a significant increase in supply chain performance and management publications identified as core elements of the topic and practice. Furthermore, the research emphasized the importance of agility, risk management, resilience, and information sharing in improving supply chain performance. These results contributed significantly to understanding the factors driving the evolution of supply chain performance and offered valuable insights for academics and practitioners addressing the dynamics, particularly in the context of improving organizational success in the challenging digital era.